Management of genetic erosion: The (successful) case study of the pear (Pyrus communis L.) germplasm of the Lazio region (Italy) - Draga, Samela; Palumbo, Fabio; Miracolo Barbagiovanni, Immacolata; Pati, Francesco; Barcaccia, Gianni (Frontiers in Plant Science, 2023)
Pyrus communis L. is an important temperate fruit with high nutritional and economic value. Italy, as the largest pear producer in the EU and second in the world, has a particularly rich germplasm characterized by hundreds of local varieties. The Lazio Region was the first Italian region to start programs focused on safeguarding varieties at risk of extinction and has started a massive census of fruit varieties by combining molecular data and productive-territorial information. In this study, 311 pear accessions collected from the five provinces of the Lazio region were genetically characterized by the means of nine simple sequence repeat (SSR) markers, eight of which were recommended by the European Cooperative Programme for Plant Genetic Resources (ECPGR). The SSR analysis revealed 250 unique genotypes and 14 cases of synonymies, namely, accessions with different names but identical molecular profiles (100% genetic similarity). The microsatellite set showed a high polymorphism information content (PIC; mean PIC=0.77) and an exceptionally high discrimination power (DP = 0.99), making it particularly efficient both for the study of genetic diversity and for the prediction of the degree of ploidy. Notably, 20% of the accessions displayed triallelic profiles (i.e., accessions having ≥2 loci with a third allele), while the remaining accessions were diploids. These results were further confirmed by flow cytometry data analysis. Standardization of the molecular analyses at the national and international levels and harmonization of the SSR sets used for germplasm characterization are of paramount importance for producing molecular profiles useful for registration and variety maintenance.